Analisis Implementasi Kebijakan Pendidikan English Day Di SMP IT Nurul Ilmi - Ezra Aisaura; M Arif Pratama Manurung; Maulida Tri Puspita; Dea Anisha (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to analyze the implementation of the English Day Education Policy at Nurul Ilmi IT Middle School. This type of research is empirical research, namely research with field data as the main data source. This type of research obtains data using field research, namely by observation, the researcher makes on-site observations of the research object to be observed using the five senses.The research results concluded that the implementation of English as an international language has an important role in global communication, access to educational and information resources, as well as career opportunities in the future. By implementing the English Day policy, schools strive to create an environment that supports the active use of English inside and outside the classroom. Through this policy, it is hoped that students will be more confident and skilled in speaking, listening, reading and writing in English.